Development of a powermeter for a bicycle - II - Chia, Alvin Wen Chien. (2012)
Cycling has evolved from a mode of transportation into sports. While light weight and durable construction of bicycle and accompanying accessories are much desired in sports, there are more emphasize being placed on the feedback provided to the rider for them to monitor their efficiency. Among the feedbacks given by the monitoring accessories on the bicycle, paddling efficiency turns out to be one of the most important parameter to the riders into sports, in which the efficiency can be measured in terms of cadence and force input into the crank of the bicycle.